2012
DOI: 10.1155/2012/389491
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Relaxation Phenomena of Polylactic Acid with -Crystalline Chitin

Abstract: -crystalline chitin was added to polylactic acid (PLA), and this PLA was then heat-treated at for one minute. The crystallinity of the heat-treated PLA increased to more than 40%, and its crystallization speed also increased significantly. The temperature dependency of these materials’ relative permittivity () and relative dielectric loss factor () was also examined. The dielectric absorption peak value in curve of the PLA to which chitin was added and was smaller than that of PLA without chitin. Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…The fitted $ value for the "-process varied in a narrow range of 0.48-0.51 over 298-500 K, which is close to the $ value of 0.51 for the "-process at 353 K in mostly amorphous PLA. 79 A much smaller $ (0.23) was obtained for the fast decay at 298 K, suggesting a much broader distribution of relaxation modes for the $-process. Above T g , the calculated relaxation times (J) were 0.6 ns at 500 K and 67 ns at 400 K. A broad-band dielectric relaxation experiment by Mijovic and Sy 77 gave J = ∼0.3 ns at 452 K in amorphous L-PLA.…”
Section: Molecular Mobility In Pla Glassesmentioning
confidence: 55%
See 1 more Smart Citation
“…The fitted $ value for the "-process varied in a narrow range of 0.48-0.51 over 298-500 K, which is close to the $ value of 0.51 for the "-process at 353 K in mostly amorphous PLA. 79 A much smaller $ (0.23) was obtained for the fast decay at 298 K, suggesting a much broader distribution of relaxation modes for the $-process. Above T g , the calculated relaxation times (J) were 0.6 ns at 500 K and 67 ns at 400 K. A broad-band dielectric relaxation experiment by Mijovic and Sy 77 gave J = ∼0.3 ns at 452 K in amorphous L-PLA.…”
Section: Molecular Mobility In Pla Glassesmentioning
confidence: 55%
“…Thus, the correlation functions in Figure were fitted with one (at T > T g ) or two (at T < T g ) KWW functions. The fitted β value for the α‐process varied in a narrow range of 0.48–0.51 over 298–500 K, which is close to the β value of 0.51 for the α‐process at 353 K in mostly amorphous PLA . A much smaller β (0.23) was obtained for the fast decay at 298 K, suggesting a much broader distribution of relaxation modes for the β‐process.…”
Section: Resultsmentioning
confidence: 90%
“…The author is pursuing the possibility of using PLA as an electrically insulating material and has already found that it has excellent electrically insulating properties at temperatures that range from normal room temperature to 60 ∘ C [6,7]. However, it is known that PLA becomes a poor electrical insulator over 60 ∘ C. The authors added a nucleating agent made of -crystalline chitin particles, extracted from squid gladii, to PLA and found that this moderates the decrease in electrical insulation of PLA at temperatures over 60 ∘ C [8]. As PLA is a hard resin, it has to be softened before it can be used as electrical wire sheathing.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the internal structure of a polymer part affects the dielectric behaviour and was described for varied polymers [30][31][32][33][34]. In the case of polyamide 66 there are three relaxation peaks known [21].…”
Section: Introductionmentioning
confidence: 99%